Edukasi Bencana sebagai Upaya Peningkatan Kapasitas Bencana Penyandang Disabilitas Netra di Kabupaten Banyuwangi - Zulfa, Alfiatus; Bachri, Syamsul; Suharto, Yusuf (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Disaster awareness is a key factor in improving individual preparedness for disaster threats, especially for people with visual impairments, including vulnerable groups who require an educational approach tailored to the characteristics of visual impairment. Therefore, this study aims to increase inclusive disaster awareness for people with visual impairments in Banyuwangi Regency, which has a high disaster risk index. Method: The method used was Participatory Action and Learning for Sustainability (PALS), which involved 10 active community participation in four stages, namely awareness raising, capacity building, mentoring, and institutionalization. Results: The study showed that the level of disaster awareness among people with visual impairments was low. The implementation of outreach using accessible media increased participants' understanding of the types of disasters and independent evacuation measures, although obstacles were encountered in the field, such as variations in educational backgrounds, language sensitivity, and limited technological literacy. This was demonstrated by an increase in the average pre-test score, which was initially low (32.5), to 91.5 in the post-test, or an increase of 59 points. The increase in knowledge levels was also evidenced by the Normalized Gain (N-gain) calculation results, with an average in the high category (g>0.7), proving that there was no knowledge gap. Conclusion: Improving inclusive disaster awareness requires continuous education, information media tailored to the characteristics of disabilities, and cross-sectoral support to achieve equitable disaster preparedness.